PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA ADABIAH 2 PADANG - Putri, Salsa Dilla (Departemen Matematika, 2023)
An understanding of mathematical concepts really helps students gain a good foundation for other basic skills such as reasoning, communication, communication and problem solving. The reality on the ground presentation that concepts understanding in mathematical by students is still weak. Lack understanding of concepts was also found during daily assessments with trigonometry material in class XI MIPA SMA Adabiah 2 Padang. The solution to this problem is the application of a jigsaw cooperative learning model. The research purpose was to analyze whether concepts understanding in mathematical by students who learned using the Jigsaw cooperative learning model was better than direct learning and to describe the development concepts understanding in mathematical by students during the application of the Jigsaw cooperative learning model. The research type is quasy experiment and descriptive research and the research design is static group comparison. While the population is all students of class XI MIPA Adabiah 2 Padang. The instruments used are quizzes and tests of concepts understanding in mathematical. Quiz data analysis resulted in the conclusion that there was a development of each indicator of concepts understanding in mathematical by students during the application of the jigsaw model. The results of the hypothesis show that reject because . So it means that concepts understanding in mathematical by students who learn using the model of Jigsaw cooperative learning is better than using learning by directed.Keywords– Cooperative Learning Model Type Jigsaw, Understanding Of Mathematical Concepts